Development of Fetal Movement between 26 and 36-Weeks’ Gestation in Response to Vibro-Acoustic Stimulation - Grant-Beuttler, Marybeth; Glynn, Laura M.; Salisbury, Amy L.; Davis, Elysia P.; Holliday, Carol; Sandman, Curt A. (Frontiers in Psychology, 2011)
Background: Ultrasound observation of fetal movement has documented general trends in motor development and fetal age when motor response to stimulation is observed. Evaluation of fetal movement quality, in addition to specific motor activity, may improve documentation of motor development and highlight specific motor responses to stimulation. Aims: The aim of this investigation was to assess fetal movement at 26 and 36 weeks gestation during three conditions (baseline, immediate response to vibro-acoustic stimulation (VAS), and post-response). Design: A prospective, longitudinal design was utilized. Subjects: Twelve normally developing fetuses, 8 females and 4 males, were examined with continuous ultrasound imaging. Outcome measures: The Fetal Neurobehavioral Coding System (FENS) was used to evaluate the quality of motor activity during 10-second epochs over the three conditions. Results: Seventy-five percent of the fetuses at the 26 week assessment and 100% of the fetuses at the 36 week assessment responded with movement immediately following stimulation. Significant differences in head, fetal breathing, general, limb, and mouthing movements were detected between the 26 week and 36 week assessments. Movement differences between conditions were detected in head, fetal breathing, limb, and mouthing movements. Conclusions: Smoother and more complex movement was observed with fetal maturation. Following VAS stimulation, an immediate increase of large, jerky movements suggest instability in fetal capabilities. Fetal movement quality changes over gestation may reflect sensorimotor synaptogenesis in the central nervous system, while observation of immature movement patterns following VAS stimulation may reflect movement pattern instability.